Students Attitude toward Correction - Fitriana, Rinda (Script Journal: Journal of Linguistic and English Teaching, 2017)
Studentsâ attitudes influence their decision to whether or not accept the teachersâ feedback. Therefore, questionnaire was administered to one hundred and ninety-six twelfth grade of vocational high school students, wherein, ten of them were involved in interview, to figure out their perspective concerning to the teachersâ correction on their oral production. From both instruments, it is found that the students preferred the teachers as the correctors, although, they did not mind for peer correction. They also expected the teachers to give correction at every time they did error and for all types of errors. Additionally, students agreed that teachersâ personality and their way of teaching influenced their willingness to accept the corrective feedback.